Intravenous administration of anti-inflammatory mesenchymal stem cell spheroids reduces chronic alcohol intake and abolishes binge-drinking - Ezquer, Fernando (Sci Rep, 2018)
Chronic alcohol intake leads to neuroinflammation and astrocyte dysfunction, proposed to perpetuate alcohol consumption and to promote conditioned relapse-like binge drinking. In the present study, human mesenchymal stem cells (MSCs) were cultured in 3D-conditions to generate MSC-spheroids, which greatly increased MSCs anti-inflammatory ability and reduced cell volume by 90% versus conventionally 2D-cultured MSCs, enabling their intravenous administration and access to the brain. It is shown, in an animal model of chronic ethanol intake and relapse-drinking, that both the intravenous and intra-cerebroventricular administration of a single dose of MSC-spheroids inhibited chronic ethanol intake and relapse-like drinking by 80–90%, displaying significant effects over 3–5 weeks. The MSC-spheroid administration fully normalized alcohol-induced neuroinflammation, as shown by a reduced astrocyte activation, and markedly increased the levels of the astrocyte Na-glutamate (GLT-1) transporter. This research suggests that the intravenous administration of MSC-spheroids may constitute an effective new approach for the treatment of alcohol-use disorders.